Methods of estimation of weights - Podvezko, Valentinas; Podviezko, Askoldas (Lietuvos matematikos rinkinys, 2014)
The purpose of using quantitative multiple criteria decision making (MCDM) methods is to identify the best alternative from the ones considered, or to rank the min order of preference in terms of a chosen objective of evaluation. One of major steps of framework of these methods is estimation of weights of criteria, which will be accounted in the research. The reason for using weights is difference of importance of criteria in terms of the objective of evaluation. In the paper different subjective methods of estimation of weights of criteria are discussed, objective and cumulative weights are covered as well.